Process Optimization for Development of Guar Gum-Based Biodegradable Hydrogel Film Using Response Surface Methodology - Junaid Aman; Navin Chandra Shahi; Umesh Chandra Lohani; Divya Balodhi; Rajat Singh; Naveen Kumar; Mohd Ishfaq Bhat; Avvaru Praveen Kumar (Bioinorganic Chemistry and Applications)
In the current study, a guar-gum-based biodegradable hydrogel film was prepared using an initiator (potassium persulfate), crosslinker (N-N methyl bis acrylamide), and plasticizer (glycerol) for packaging of fruits and vegetables. The effect of independent variables (initiator, crosslinker, and plasticizer) on the biodegradation (% wt. loss), color difference (ΔE), hardness (N), swelling index (%), and transparency (%) of the film was studied using Box–Behnken design, random surface methodology (RSM). The results showed significant effects on all the abovementioned parameters, and it was observed that the developed model was accurate, with a prediction error of only −3.19 to 2.99%. The optimized formulation for the preparation of hydrogel film was 0.15% initiator, 0.02% crosslinker, and 2.88% plasticizer exhibiting satisfactory biodegradability, color difference, hardness, swelling index, and transparency. Results showed that a guar-gum-based biodegradable hydrogel film has adequate physical, optical, and biodegradable properties and can be successfully utilized in the food packaging industry.